Characterization of water in the selected coastal areas in Lingayen gulf of Pangasinan - Cancino, Lina T. (Virgen Milagrosa University Foundation : [s.n.], 2019)
The water quality of the selected coastal areas in Lingayen Gulf of Pangasinan were assessed in terms of their primary parameters of physical chemical and biological characteristics in combination with the types of animals, plants and algae found in each sampling station: Bolinao, Alaminos, Sual, Lingayen and San Fabian. Results showed that the physical characteristic of water samples taken from Bolinao and Sual passed the criteria of DENR. Alaminos coastal water failed in color. Alaminos, Lingayen and San Fabian values exceeded the threshold limit in Total Suspended Solids (TSS). For the chemical characteristics, all the results were favorable for aquatic life. In terms of biological characteristics. water samples taken from Bolinao, Alaminos, Sual and San Fabian were contaminated with fecal coliform, but Lingayen met the criteria. Signs of water degradation were evident in the results of laboratory analysis as one or two parameters of each did not meet the DENR standard. Bolinao obtained the greatest number for the types of animals present. Also, the four sampling stations have the same number and varieties of plants and algae present except for Lingayen which had the least types of animals and no presence of plants and algae. 103 The presence of plastics along the coastal areas is the topmost observation, Destructive fishing is still being practiced despite the laws and policies formulated. Disposal of wastes in the river and seas, run-offs from the households, tourists' activities, the presence of congested fish cages and pens are the contributory factors that affect the water quality which leads to the threatening of marine life. These mentioned activities were all being practiced due to lack of political will, irresponsible citizens, insufficient knowledge and poverty based on the survey conducted. The study recommended the following; massive information dissemination through the distribution of the information material must be conducted. Aggressive evaluation and monitoring of point and non-point sources of water pollutants by conducting an inventory of the major pollution sources must also be done. Review of policies, close monitoring and enforcement of laws, is also recommended to ascertain the quality of water along the coastal areas in Lingayen Gulf of Pangasinan so that environmental legislation should be implemented strictly down to the household level.
Bibliography: pages 159-165.
CHED-La Union
Keywords: Water quality